2015
DOI: 10.1186/s13000-015-0255-7
|View full text |Cite
|
Sign up to set email alerts
|

miR-203 inhibition of renal cancer cell proliferation, migration and invasion by targeting of FGF2

Abstract: BackgroundRenal cell carcinoma (RCC) is one of the leading causes of cancer related mortality worldwide. Increasing evidence has shown that microRNAs function as oncogenes or tumor suppressors in human malignancies, but the roles of miR-203 in human RCC is still unclear.MethodsFirst, quantitative real-time PCR (qRT-PCR) was performed to detect miR-203 expression in renal cancer cell lines and clear cell RCC (ccRCC) specimens. Then, the association of miR-203 expression with clinicopathological features and sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
46
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 29 publications
5
46
0
Order By: Relevance
“…In this study, we found that miR-203-3p, combined with the 3' UTR region of FGF2, could exert a direct regulatory effect. These results are consistent with those of previous studies [35,36] , and they explain why miR-203 can affect the proliferation, invasion, and migration of pancreatic cancer cells. However, we also found that downregulation of miR-203 inhibited AsPC-1 cell apoptosis, but overexpression of FGF2 had no significant effect on cell viability.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this study, we found that miR-203-3p, combined with the 3' UTR region of FGF2, could exert a direct regulatory effect. These results are consistent with those of previous studies [35,36] , and they explain why miR-203 can affect the proliferation, invasion, and migration of pancreatic cancer cells. However, we also found that downregulation of miR-203 inhibited AsPC-1 cell apoptosis, but overexpression of FGF2 had no significant effect on cell viability.…”
Section: Discussionsupporting
confidence: 93%
“…For example, miR-203 is overexpressed in pancreatic cancer and not in normal pancreatic tissue and chronic pancreatitis, suggesting that miR-203 may be related to specific characteristics of tumors and their behavior [18] . Other studies have suggested that FGF2 expression may be affected by miR-203 [19,20] . However, the relevant mechanisms of action and signaling pathways in pancreatic cancer remain unknown.…”
Section: Introductionmentioning
confidence: 98%
“…It is, thus, interesting to correlate these data with the fact that miR-125b was shown to directly target FGFR-2 in a psoriasis model, suggesting another mechanism by which this miRNA could inhibit both osteoblastic differentiation and carcinogenesis ( Figure 6) [75]. In addition, miR-203 was identified as being a direct inhibitor of FGF2 in renal cancer [178]. In accordance with these results, it was also highlighted that FGFR-2 promotes osteogenic differentiation through the serine/threonine kinase protein kinase C alpha (PKCα) and the ERK1/2 pathways in murine MSCs [179].…”
Section: The Fibroblast Growth Factor (Fgf) Pathwaymentioning
confidence: 89%
“…Aberrant expression of diverse miRNAs in tumor samples has been determined as an efficient diagnostic and prognostic biomarker in human malignancies, including OS [10]. In addition, some functional miRNAs have been indicated as potential targets in tumor targeted therapy through modulating oncogenes or tumor suppressor genes [11,12]. Thus, we believed that the investigation of miRNAs for their clinical significance and biological function could improve the prognosis and treatment of OS.…”
Section: Introductionmentioning
confidence: 99%